Impact of production-and consumption-oriented interventions on crop varietal adoption: Cluster-randomized controlled trial evidence from northern Nigeria - Ragasa, Catherine; Oyinbo, Oyakhilomen; Ma, Ning (Wiley, 2025)
This paper evaluates the impact of three interventions (seed trial packs, consumption-oriented interventions, and agricultural training, either individually or bundled) in improving varietal turnover in northern Nigeria via a 3-year cluster-randomized controlled trial. A secondary objective of the paper is to evaluate the performance of these varieties in farmers’ fields. Results show that seed trial packs increased adoption of promoted varieties by 42%–44% of farmers and 42%–47% of maize and cowpea land area. Farmers rated production, processing, marketing, and consumption characteristics of these varieties very highly. Yields on plots with promoted varieties were significantly higher than those of farmers’ traditional varieties, ranging from 16% to 25% more for maize and 70% for cowpea in the first season, with observed yields persisting in the second season.